Radiation-resistant ultraviolet curable polyurethane films with CdSe-ZnS сore-shell nanocrystals - Kulish, N.R.; Kunets, V.P.; Narsingi, K.Y.; Manasreh, M.O.; Kunets, Vas. P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
The effect of proton fluence of different doses (up to 9×10¹⁵ protons/cm²
) on the absorption spectra of UV-cured polyurethane films doped by CdSe/ZnS nanocrystals
has been investigated. We found that the degradation of this type of protective coating is
related to the degradation of polyurethane film itself, but not the CdSe/ZnS nanoparticles.